Synthesis, structure, and reactivity of diazoketiminato complexes of platinum(II) and palladium(II): cytotoxic properties of a platinum complex - Pratihar, Jahar Lal; Shee, Biswaranjan; Pattanayak, Poulami; Patra, Debprasad; Bhattacharyya, Arindam; Puranik, Vedavati G.; Hung, C. H.; Chattopadhyay, Surajit (European Journal of Inorganic Chemistry, 2007)
{Reaction of the 2-(arylazo)anilines Ar-N = N-C6H4NH2 [
Keywords: CFD; hydro processing; scale-down; scale-up; trickle bed

Kinetic promotion of methane hydrate formation by combining anionic and silicone surfactants: scalability promise of methane storage due to prevention of foam formation - Bhattacharjee, Gaurav; Barmecha, Vivek; Kushwaha, Omkar S.; Kumar, Rajnish (Journal of Chemical Thermodynamics, 2018)
Methane storage in its solid hydrate form has recently come up as a rather attractive and low risk option for large scale storage of the gas owing to its mild storage conditions, high gas retention capacity and benign (non-explosive) character. However, it has its fair share of limitations with the slow rate of hydrate formation being one of the most prominent. The addition of surfactants like Sodium dodecyl sulfate (SDS) to the hydrate forming system significantly speeds up the process of methane hydrate formation but the large amount of foam generated by these surfactants during the process of hydrate formation and dissociation stands as a major roadblock towards the scaling up of the technology. In the current work, a small amount of a silicon based surfactant has been proposed to be used as antifoam in conjunction with an anionic surfactant SDS to eliminate the foam generation while at the same time promote the kinetics of methane hydrate formation. The idea is simple, cost effective and can be a potential game-changer in the quest to develop a commercially scalable hydrate based methane storage technology. (C) 2017 Elsevier Ltd.
Keywords: Antifoam; Gas hydrate; kinetics; Methane storage; scale-up; Silicone surfactant

CFD modelling of almond drying in a tray dryer - Chilka, Amarvir G.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2019)
Drying is important in many food processing applications, and particularly so in the dry fruits industry. This work is focused on developing computational models for simulating the drying of almonds in a tray dryer. It is important to quantitatively understand heat and mass transfer within and around a single almond particle as well as the particle-particle interactions and their implications for dryer design. In this work, we have developed a systematic CFD modelling framework for modelling almond drying in a tray dryer. A single tray filled with almonds (similar to 2 kg) were dried at three set temperatures viz., 55, 65, and 75 degrees C. Air relative humidity at the inlet and outlet locations, and the weight of almonds were measured during drying for each experiment. An additional set of experiments were conducted in which almonds were filled only in the half section of the tray, keeping the other half empty. The same amount of almonds were used, to have multiple layers of almonds in the tray, and the set temperature for the experiment was 75 degrees C. Flow, heat, and mass transfer in the tray dryer were simulated using commercial CFD software Ansys Fluent. The validated computational model was used to simulate various cases including larger and more trays. The developed approach and models will be useful to select the appropriate dryer configuration and optimize its design. The developed models will also be useful to identify suitable operation conditions for the drying of almonds as well as other food products.
Keywords: Almonds; CFD; Drying; scale-up; tray dryer

Scalable microwave-assisted continuous flow synthesis of CuO nanoparticles and their thermal conductivity applications as nanofluids - Nikam, Arun V.; Dadwal, Arun H. (Advanced Powder Technology, 2019)
We have demonstrated the novel and scalable synthesis of CuO nanoparticles by an integration of microwave and flow synthesis. The shape and size of CuO nanoparticles were tuned by changing the concentration of copper precursor. The production rate of CuO nanoparticles was found to be 5 g/h with 70% conversion of copper acetate into the CuO nanoparticles. The thermal conductivity of CuO nanofluid prepared in ethylene glycol showed linear enhancement with increase in the volume content of CuO nanoparticles produced in batch and flow reactors. (C) 2018 The Society of Powder Technology Japan. Published by Elsevier B.V. and The Society of Powder Technology Japan. All rights reserved.
Keywords: Flow synthesis; Microwave; Nanofluids; Nanoparticles; scale-up; Thermal conductivity

Design and scale-up of continuous di-nitration reaction using pinched tube flow reactor - Hussain, Arshad; Sharma, Mrityunjay; Patil, Suneha; Acharya, Roopashree B.; Kute, Mahesh; Waghchaure, Aishwarya; Kulkarni, Amol A. (Journal of Flow Chemistry, 2021)
Scale-up of the di-nitration reaction for synthesis of selective herbicide pendimethalin using only nitric acid in continuous flow is presented in this work. This work showcases an approach for smooth scale-up for an herbicide for a production capacity of 50 kg/day using a pinched tube reactor. The approach begins with the batch experiments followed by flow synthesis using a 1/8-inchSS316 helical coil tube where kinetics of the di-nitration was determined, and process optimization was done. Systematic approach was followed for quantification of heat transfer, mass transfer and residence time distribution and scale-up. Detailed scale-up methodology is presented with effect of relevant parameters for successful scale-up. Modular pilot plant with inline quenching, extraction and separation are some of the salient features presented in this work.
Keywords: continuous flow; nitration; Pinched tube; RTD; scale-up